2021
DOI: 10.1021/acs.iecr.1c01779
|View full text |Cite
|
Sign up to set email alerts
|

Insights of the Dynamic Copper Active Sites in Ethylene Oxychlorination Studied by the Multivariate UV–vis–NIR Resolution Kinetic Approach

Abstract: Monitoring and simulating the events occurring on the catalysts under the real reaction conditions has significant meaning for elucidating the dynamic changes of the active sites during the reactions and for a better understanding of the reaction mechanisms. Herein, we use the operando ultraviolet–visible and near-infrared (UV–vis–NIR) spectroscopy to study the CuCl2/γ-Al2O3-based catalyst in ethylene oxychlorination, one of the most important processes for producing vinyl chloride in the industry, to elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…37 Operando experiments have further confirmed that La does not act as an active site in participating in the redox cycle. 38 It exists in its chloride form, where Cl is directly bonded with La. La is considered as a chemical promoter to alter the electronic structure of the Cu active site by influencing the Cl bonded with La and Cu.…”
Section: Optimization Of Reaction Conditions For Bestmentioning
confidence: 99%
“…37 Operando experiments have further confirmed that La does not act as an active site in participating in the redox cycle. 38 It exists in its chloride form, where Cl is directly bonded with La. La is considered as a chemical promoter to alter the electronic structure of the Cu active site by influencing the Cl bonded with La and Cu.…”
Section: Optimization Of Reaction Conditions For Bestmentioning
confidence: 99%
“…The data correspond to the reduction (left), oxidation (middle), and hydrochlorination (right) steps, respectively. Adapted with permission from reference . Copyright 2021 American Chemical Society.…”
Section: Advances In Techniques and Methods Used To Investigate Catal...mentioning
confidence: 99%
“…In this context, operando UV–vis–NIR measurements can offer an accessible way of studying the dynamics of catalytic cycles involving species with strong visible light absorption. , This technique would be advantageous in systems with strong d–d transitions and charge transfer regions, such as Cu-halide-based systems. Researchers recently demonstrated the utility of this approach in studying the dynamics of ethylene oxychlorination on CuCl 2 –Al 2 O 3 -based catalysts . Specifically, they combined a multivariate UV–vis–NIR resolution kinetic approach (MURKA) with multivariate curve resolution (MCR) to analyze the spectroscopic evolution of the catalyst under operating conditions.…”
Section: Advances In Techniques and Methods Used To Investigate Catal...mentioning
confidence: 99%
See 1 more Smart Citation
“…Many efforts have been devoted to understanding the chemistry of the catalyst, the reaction mechanism, and the role of promoters in affecting the catalytic performance and the active sites, and also the influence of different supports on this reaction. γ-Al 2 O 3 is widely used and recognized as the superior support due to the strong interaction with CuCl 2 than the other supports like SiO 2 and α-Al 2 O 3 , enhancing the catalyst stability and minimizing the volatility of CuCl than other supports . Moreover, the interaction is quite important in the catalyst stability, especially for the Cu loss and migration.…”
Section: Introductionmentioning
confidence: 99%